Plan de Comercialización de quesos para la Asociación de Ganaderos de Saraguro, parroquia Saraguro, en el año 2024 - Loja Sánchez, Vicente Renato (2024)
The general objective of this degree project is to develop a marketing plan to improve the positioning of the fresh cheese product of the Saraguro Cattlemen's Association, Saraguro canton, Loja province, to position itself in front of the competition, keeping itself in the consumer's mind, building customer loyalty and achieving greater profitability. The development of this work focused on three specific objectives. To achieve the first objective, the current situation of the Dairy Company of the Saraguro Cattlemen's Association and its competitors was analyzed through market research, an external analysis using the PESTEL matrix, and an internal analysis to determine the company's strengths and weaknesses, in addition to a SWOT analysis and the development of a CANVAS model. To fulfill the second specific objective, an Ansoff Matrix, a business strategy and strategic marketing tool, was used to identify the company's growth opportunities. For the fulfillment of the third specific objective, through a proposed Marketing Plan, which included the development of the Business Philosophy, and matrix of tactics of marketing strategies, marketing strategies were defined to promote and sell fresh cheeses from the SARALAC Cheese Factory, of the Saraguro Cattlemen's Association, to consumers and customers, in local and 3 social networks Tik Tok, Instagram and Facebook.